Burst capacity of pipe under corrosion defects and repaired with thermosetting liner - Akram, A. (Techno Press, 2020)
This paper aims at providing insights on the use of thermosetting liner for the repair of offshore pipelines exposed to corrosion and leakage. The work which covers both experimental and numerical approaches were aspired due to the high cost of repair for pipelines, limitations of thermoplastic material and limited study of reinforced thermosetting liner. The experiment involves a destruction test called the burst test, carried out on an API 5L X42 carbon steel pipe under four case studies, namely (i) intact pipe, (ii) pipe with corrosion defect, (iii) pipe with corrosion defect and repaired with thermosetting liner and (iv) pipe with leakage and repaired with thermosetting liner. The numerical simulation was developed to first validate the experimental results and later to optimize the design of the thermosetting liner in terms of the number of layers required to restore the original strength of the pipe. The burst test shows an improvement in 23 of the burst capacity for the pipe with corrosion defects, after being repaired with a three-layer thermosetting liner. The parametric studies conducted showed that with an addition of thermosetting layers, the burst capacity improves by an average of 1.85 MPa. In conclusions, the improvement in strength can be further increased with increasing thickness of the thermosetting liner. The thermosetting liner was also determined to fail first inside the host pipe. Copyright Â© 2020 Techno-Press, Ltd.